STRATEGI WACANA REKONSILIASI DAN LEGITIMASI KEKUASAAN DALAM PIDATO PERDANA PRABOWO SUBIANTO: SEBUAH ANALISIS WACANA KRITIS - Hamiruddin Udu; Hidrawati Hidrawati (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2026)
This study examines the discursive strategies employed in Prabowo Subianto’s inaugural speech following his designation as the elected President of Indonesia in 2024. Using Teun A. van Dijk’s Critical Discourse Analysis (CDA) the study argues that the speech functions as a strategic instrument to construct political legitimacy and reconcile post-election polarization through a structured set of linguistic strategies. The primary data consist of the full transcript of the speech delivered at the General Elections Commission (KPU) Hall, analyzed through three dimensions of van Dijk’s model: textual structure, social cognition, and social context. The findings revealed; first, at the level of textual structure, the speech is constructed around macrostructures of reconciliation and inclusivity, realized through rhetorical strategies such as the neutralization of in-group/out-group polarity, the use of family metaphors, euphemism, and presuppositions that affirm electoral legitimacy. Second, at the level of social cognition, the discourse represents post-election collective mentalities—such as political fatigue and aspirations for unity—while advancing a nationalist-populist ideology characterized by anti-elitist and religious elements. Third, at the level of social context, the speech operates as a hegemonic strategy to consolidate power, achieved through the appreciation of state institutions, symbolic reconciliation with opposition groups, and the projection of populist policies focused on public welfare. This study proved that language plays an important role Indonesian political discourse by demonstrating how linguistic resources are mobilized for strategic political purposes within an electoral democratic context.